The Improving Descriptive Writing by Using Chat-GPT in University - Najah, Luluk Lailatun; Ghozali, Imam (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2024)
This study investigates the use of Chat-GPT to enhance descriptive writing skills in higher education. The research involved students utilizing Chat-GPT to support their writing process, leading to a significant improvement in their work. The mean score for descriptive writing increased from 64 to 85.5, marking a 33.6% enhancement. The analysis revealed that Chat-GPT effectively improved sensory detail, clarity, and cohesion while boosting students' enthusiasm for writing. Successful implementation relied on careful integration with structured guidance. While individual responses varied, using Chat-GPT as a complement to traditional methods yielded the best outcomes. The findings indicate that when implemented properly, Chat-GPT can serve as an effective tool for developing students' descriptive writing skills. However, its success is contingent upon thoughtful integration and adjustment to individual needs. This research paves the way for further exploration into the role of AI in education, particularly in cultivating academic writing skills.